Using Support Vector Machine on EEG for Advertisement Impact Assessment - Wei, Zhen; Wu, Chao; Wang, Xiaoyi; Supratak, Akara; Wang, Pan; Guo, Yike (Frontiers in Neuroscience, 2018)
The advertising industry depends on an effective assessment of the impact of advertising as a key performance metric for their products. However, current assessment methods have relied on either indirect inference from observing changes in consumer behavior after the launch of an advertising campaign, which has long cycle times and requires an ad campaign to have already have been launched (often meaning costs having been sunk); or through surveys or focus groups, which have a potential for experimental biases, peer pressure, and other psychological and sociological phenomena that can reduce the effectiveness of the study. In this paper, we investigate a new approach to assess the impact of advertisement by utilizing low cost EEG headbands to record and assess the measurable impact of advertising on the brain. Our evaluation shows desired performance of our method based on user experiment with 11 recruited subjects after watching 220 different advertisements. We believe the proposed method can be further developed to a general and scalable methodology that can enable advertising agencies to assess impact rapidly, quantitatively, and without bias.